Increasing youth competency in creating digital content using Canva for digital marketing - Notonegoro, Hamdan Akbar; Nurhamida, Nurhamida; Sunengsih, Neneng; Abdullah, Syarif; Jannah, Miftahul; Qolbi, Fatimah Nurul; Salamah, Khadijah Barorotus (Journal of Community Service in Science and Engineering (JoCSE), 2024)
This activity aims to accommodate teenagers' high curiosity about the development of digital technology, especially in creating valuable content for marketing their products on the digital market. For these reasons, UPPA Hamzah held digital competency training for teenagers in RW 02, Cipayung sub-district, Ciputat District. This training activity consists of two sessions: a photography training session and training on using the Canva application to create digital content. This activity was carried out independently and presented three speakers from different backgrounds. Participant participation was identified based on the initial target number of participants, the number of participants who registered and attended the event, and the age range and gender ratio of the participants. In this activity, participants were trained to create digital content from the results of their photography using the Canva application installed on their cell phones. Kegiatan ini bertujuan untuk mengakomodir tingginya rasa keingintahuan remaja terhadap perkembangan teknologi digital, terutama dalam pembuatan konten yang bermanfaat untuk memasarkan produk-produk mereka di pasar digital. Berdasarkan alasan tersebut, UPPA Hamzah mengadakan pelatihan kompetensi digital untuk para remaja di RW 02 kelurahan Cipayung Kecamatan Ciputat. Kegiatan pelatihan ini terdiri dari dua sesi, yaitu sesi pelatihan fotografi dan pelatihan penggunaan aplikasi Canva untuk membuat konten digital. Kegiatan ini dilaksanakan secara swadaya dan menghadirkan tiga narasumber dari latar belakang yang berbeda. Partisipasi peserta yang hadir diidentifikasi berdasarkan target awal jumlah peserta dengan banyaknya peserta yang mendaftar dan hadir dalam acara, serta rentang usia dan rasio gender para peserta. Pada kegiatan ini, para peserta dilatih untuk mampu membuat konten digital dari hasil pengambilan fotografi sendiri menggunakan aplikasi Canva yang ditanam pada ponsel mereka.